Effect of Some Aluminum Salts - Amine Ionic Liquids on Several Serum Human Parameters and Bacterial Growth of Klebsiella pneumoniae and Staphylococcus aureus - Hasan, Bassam B; Abood, Hadi M A; Mohamed, Nadira S (Al-Nahrain Journal of Science, 2018)
The advantages of pharmaceutics and biological activity of some ionic liquids (ILs) on human serum (HS) and bacterial growth were studied. The effect of aluminum nitrate-acetamide (AN-Ac) and aluminum ammonium sulfate-urea (ammonium alum-urea) ionic liquids were studied on two types of bacterial species gram negative (K.pneumoniae) and gram positive (Staph.aureus). The results showed that the key factors of inhibition are the type, structures, kind of anion and cation of ILs, water miscibility and concentration of ILs and the type of microorganism in both solid and liquid media. Inhibition of bacteria growth was observed to be decreased with decreasing the quantities of (AN-Ac) and (ammonium alum-urea) ILs. The inhibition zone (The Kirby-Bauer Disk Diffusion Test), beside the optical density were measured at 600 nm for bacterial broth incubated at 37 ºC for 24hrs with different concentrations of ionic liquids of (2, 5, 10, 20)% (v/v). Subsequently, the results of optical densities were calculated as colony forming units (CFUs). The concentration of ILs was calculated practically until it reached the optimal concentration of 2% (v/v). This concentration caused no variation on serum parameters likes sugar, lipid profile, protein, liver functions, kidney functions, and electrolytes, obtained by using Automatic biochemistry analyzers technique.